THE EFFECTIVENESS OF GIVING BADUY HONEY ON INCREASED HEMOGLOBIN IN PREGNANT WOMEN AT UPT PUSKESMAS DTP SAKETI - Nuranissa, Hana; Yuningsih, Sukarni Setya (HEARTY, 2024)
Background: Anemia in pregnancy is usually caused by a lack of nutritional intake during pregnancy where the need for iron increases. One effort is to consume natural ingredients such as honey. Honey has many ingredients that are beneficial for the body, especially pregnant women, where 100 grams of honey contains 0.42 mg of fe/iron and 2 micrograms of folate, 0.5 mg of vitamin C. Research purposes: To find out the benefits of giving Baduy honey in increasing hemoglobin levels in pregnant women. Research methods: This type of research is quantitative research, The research method used by the author is a quasi-experimental method (Quasi Experiment). "This research method is a way of solving a research problem that is carried out in a planned and careful manner to obtain facts and conclusions that can be understood. The research design used is a pretest-posttest with control group design to determine the effect of treatment in the intervention group by comparing it with the control group. This design uses 2 experimental groups and a control group. Research result: The results of the chi square test obtained a value of p=0.002, which means that if the α value <0.05 the value has a significant influence, so it can be concluded that there is a significant influence between the consumption of Baduy honey on the incidence of anemia in TM III pregnant women at the Saketi Health Center. Conclusion: There is a significant influence between the consumption of Baduy honey on the incidence of anemia in TM III pregnant women at the Saketi Community Health Center.